Association of Inflammatory Factors and Calcium Metabolism With Arthritis in Patients With Inflammatory Bowel Disease: Evidence From Mediated Mendelian Randomization - Sinan Xiao; Kairong Su; Hongliang Gao; Chenyang Qiao; Sumei Sha; Xin Liu; Haitao Shi (Mediators of Inflammation)
Conclusion: This study establishes the causal effect of IBD on AS, PsA, and ReA. The absence of significant mediation effects suggests that IBD-associated gut dysbiosis, systemic inflammation, and calcium metabolic disturbances may not directly drive arthritis pathogenesis, challenging their utility as predictive biomarkers for arthritis development in IBD patients.